Bromelain: from Production to Commercialisation - Aizi Nor Mazila, Ramli; Tuan Norsyalieza, Tuan Aznan; Rosli, Md. Illias (Wiley, 2016)
Bromelain is a mixture of proteolytic enzymes found in pineapple (Ananas comosus) plants. It can be found in several parts of the pineapple plant, including the stem, fruit, leaves and peel. High demand for bromelain has resulted in gradual increases in bromelain production. These increases have led to the need for a bromelain production strategy that yields more purified bromelain at a lower cost and with fewer production steps. Previously, bromelain was purified by conventional centrifugation, ultrafiltration and lyophilisation. Recently, the development of more modern purification techniques such as gel filtration, ion exchange chromatography, affinity chromatography, aqueous two-phase extraction and reverse micelle chromatography has resulted in increased industrial bromelain production worldwide. In addition, recombinant DNA technology has emerged as an alternative strategy for producing large amounts of ultrapure bromelain. An up-to-date compilation of data regarding the commercialisation of bromelain in the clinical, pharmaceutical and industrial fields is provided in this review.